The Development of Activity-Based Learning Model to Enhance Research skills for Pre-service Teachers of Industrial Education, Faculty of Industrial Education and Technology, KMUTT - Wongdee, Prapassorn (Humanities, Arts and Social Sciences Studies, 2019)
This research aimed to 1) develop an activity-based learning model to enhance research skills for pre-service teachers of industrial education, Faculty of Industrial Education and Technology, King Mongkut’s University of Technology Thonburi (KMUTT) and 2) study the effect of activity-based learning on research skills of pre-service teachers. The sample was divided into two groups; the first sample group was 29 pre-service teachers who were studying in the first semester of the 2015 academic year and the second sample group was 50 pre-service teachers who were studying in the first semester of the 2016 academic year in the Faculty of Industrial Education, KMUTT. The results found that 1) The model of activity-based learning to enhance research skills of pre-service teachers was created from the integration of principles and research methodology including the practice of every step of research methodology. The learners learned how to gain research skills by “Practice of Doing Research”. The teachers facilitated and mentored doing research under the concept of blended learning. The classroom activity focused on practicing research process as the goal weekly. A Facebook group was used for presenting instructional media, media for lecturing, examples of research, classroom learning activity, and for being a center of communication and counseling outside the classroom. The content was classified into seven modules; (1) stating problems of research, (2) reviewing literature, (3) identifying research limitations, (4) research instruments, (5) research methodology, (6) data collection and analysis, and (7) research report. The learning management lasted 15 weeks long. Each module was composed of 5 steps; 1) knowing objectives, 2) learning principles, 3) practicing research, 4) presenting research, and 5) evaluating research, suggestion, and improvement (Formative Assessment). The research was evaluated by two experts to check the completeness and accuracy of the research (summative evaluation) after the 15th week. 2) The second group of samples had research skills significantly higher than the first sample group who were at the level of .05. The second group samples had research skills at the level of “very good” and the first group samples had research skills at the level of “good”. The samples reflected that they did not only gain knowledge and research skills but also had skill for searching for information, team-working skill and self-directed skill to achieve the goals and apply the knowledge for studying other courses such as project work.